2016
DOI: 10.1111/aji.12546
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of helper, cytotoxic, and regulatory T cells in the decidua from miscarriage

Abstract: Activation of IFN-γ(+) Tc and Treg cells in the decidua might be associated with the pathophysiology underlying MN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…1,8 It is therefore not surprising that Treg cell levels in decidua are low in inevitable spontaneous abortion of normal karyotype embryos compared to normal levels in elective termination decidua and in decidua associated with abnormal karyotype embryos. 11 So is missed abortion a distinct entity unrelated to the pathogenesis of spontaneous abortion, or are there factors in missed abortions that prevent progression to clinical abortion? 1,8 By contrast, in the decidua of missed abortion cases, which have not become inevitable, with a normal karyotype embryo Ebina et al reported an increase in Foxp3 + CD4 + CD25 high Tregs and an increase in CD8 + IFNγ + "effector" T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8 It is therefore not surprising that Treg cell levels in decidua are low in inevitable spontaneous abortion of normal karyotype embryos compared to normal levels in elective termination decidua and in decidua associated with abnormal karyotype embryos. 11 So is missed abortion a distinct entity unrelated to the pathogenesis of spontaneous abortion, or are there factors in missed abortions that prevent progression to clinical abortion? 1,8 By contrast, in the decidua of missed abortion cases, which have not become inevitable, with a normal karyotype embryo Ebina et al reported an increase in Foxp3 + CD4 + CD25 high Tregs and an increase in CD8 + IFNγ + "effector" T cells.…”
Section: Introductionmentioning
confidence: 99%
“…1,8 By contrast, in the decidua of missed abortion cases, which have not become inevitable, with a normal karyotype embryo Ebina et al reported an increase in Foxp3 + CD4 + CD25 high Tregs and an increase in CD8 + IFNγ + "effector" T cells. 11 So is missed abortion a distinct entity unrelated to the pathogenesis of spontaneous abortion, or are there factors in missed abortions that prevent progression to clinical abortion?…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that Treg migration from the peripheral blood toward the decidua decreases in cases of miscarriage with a normal or abnormal embryo karyotype (49,50). Also an intrinsic deficiency in peripheral blood Tregs in RPL is associated with diminished IL-2 and TGF-β secretion whereas decidual Tregs have elevated interferon (IFN)-γ expression (51). Tregs that express insufficient FOXP3, due to polymorphisms in the promoter region, may be phenotypically plastic and convert into Th17 and then could directly contribute to the pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Migration of CD8 + T lymphocytes to the decidua is facilitated by an increase in the expression of CXCR3 [21] and CCR5 [63,93]. CXCR3 ligands produce decidual stromal cells: CXCL9 (MIG), CXCL10 (IP-10), CXCL11 (I-TAC) [30]. CXCL9 is expressed in the placenta and in the chorioamniotic membrane, is found in the bloodstream, and the increased production of this molecule is associated with premature delivery and low foetal weight [29,62,65,105,115].…”
Section: Differentiation Of Cd8 + T Lymphocytesmentioning
confidence: 99%